2014
DOI: 10.1111/apt.12912
|View full text |Cite
|
Sign up to set email alerts
|

End‐stage methotrexate‐related liver disease is rare and associated with features of the metabolic syndrome

Abstract: SummaryBackgroundMethotrexate (MTX) is one of the most frequently prescribed drugs in contemporary medicine with a well‐recognised hepatotoxic potential, for which stringent laboratory and histological surveillance has long been advocated.AimTo estimate the population burden of end‐stage methotrexate‐related liver disease (MTX‐LD) in the United States and identify independent host risk factors for this disease entity.MethodsWe analysed the records of all individuals who had been listed for, and/or received, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 73 publications
1
39
0
2
Order By: Relevance
“…In a study enrolling 24 patients on long-term MTX therapy for psoriasis, serial liver biopsies revealed that non-alcoholic steatohepatitis (NASH) is an important cause of liver injury in such patients, and a high cumulative dose of MTX alone can lead to a NASH-like liver injury pattern19. This observation was corroborated by a recent analysis of individuals who received or had been listed for liver transplantation in the US, which shows that the risk factor profile of end-stage MTX-related liver disease is similar to that of NASH20. In our recent study of RA patients with CHB4, we speculated that compared to MTX users, MTX non-users had less severe disease activity of RA, which was associated with higher body mass index2122.…”
Section: Discussionmentioning
confidence: 87%
“…In a study enrolling 24 patients on long-term MTX therapy for psoriasis, serial liver biopsies revealed that non-alcoholic steatohepatitis (NASH) is an important cause of liver injury in such patients, and a high cumulative dose of MTX alone can lead to a NASH-like liver injury pattern19. This observation was corroborated by a recent analysis of individuals who received or had been listed for liver transplantation in the US, which shows that the risk factor profile of end-stage MTX-related liver disease is similar to that of NASH20. In our recent study of RA patients with CHB4, we speculated that compared to MTX users, MTX non-users had less severe disease activity of RA, which was associated with higher body mass index2122.…”
Section: Discussionmentioning
confidence: 87%
“…MTX is associated with an increased incidence of negative liver events (RR, 2.19; 95% CI, 1.73–2.77) 97 through oxidative stress, 98 and thus hepatotoxic drugs and preexisting liver disease are contraindications to MTX use. This includes suspected or undiagnosed liver disease, as in patients who are heavy alcohol users and obese (body mass index >30 kg/m 2 ), diabetic and hyperlipidemic patients, of whom the latter three are at increased risk of nonalcoholic fatty liver disease.…”
Section: Immunomodulatorsmentioning
confidence: 99%
“…This includes suspected or undiagnosed liver disease, as in patients who are heavy alcohol users and obese (body mass index >30 kg/m 2 ), diabetic and hyperlipidemic patients, of whom the latter three are at increased risk of nonalcoholic fatty liver disease. 94,98 Known chronic liver diseases, particularly chronic viral hepatitis B (HBV) and C (HCV) are also contraindications. Although rare and more often associated with anti-TNF-α agents, reactivation of resolved HBV infection in MTX-treated patients has been reported, 99 although a recent report claimed no reactivation in an HBV-infected population with rheumatological diseases in Thailand.…”
Section: Immunomodulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, en la AR se ha observado una tasa muy baja de hepatotoxicidad 55 , y directamente en las EII una dosis acumulada media de más de 2,5 gramos de MTX solo se asoció a un grado leve de fibrosis en uno de veinte pacientes estudiados por biopsia 60 . De hecho datos indirectos muy recientes sugieren que la hepatotoxicidad grave por MTX es realmente rara 61 . En las EII disponemos de un metaanálisis reciente, en el que si se medía la hepatotoxicidad por la hipertransaminasemia (> x2 el valor normal), su incidencia era de 0,9 pacientes/mes, con una tasa de retirada del tratamiento de 0,8 pacientes/mes 62 63 .…”
Section: Toxicidadunclassified